2022
DOI: 10.3390/diagnostics12092064
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Diffuse Midline Gliomas: An Unfinished Puzzle

Abstract: Diffuse midline glioma (DMG) is a heterogeneous group of aggressive pediatric brain tumors with a fatal prognosis. The biological hallmark in the major part of the cases is H3K27 alteration. Prognosis remains poor, with median survival ranging from 9 to 12 months from diagnosis. Clinical and radiological prognostic factors only partially change the progression-free survival but they do not improve the overall survival. Despite efforts, there is currently no curative therapy for DMG. Radiotherapy remains the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 130 publications
(120 reference statements)
0
21
0
1
Order By: Relevance
“…The description of the rationale and results of such new therapeutic approaches is beyond the scope of this review. That said, so far, none of the recent clinical trials with published results has demonstrated a relevant impact on improving survival ( 8 ), although many of them are still ongoing and many others are not active yet. Much hope and scientific effort are being invested in those modern approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The description of the rationale and results of such new therapeutic approaches is beyond the scope of this review. That said, so far, none of the recent clinical trials with published results has demonstrated a relevant impact on improving survival ( 8 ), although many of them are still ongoing and many others are not active yet. Much hope and scientific effort are being invested in those modern approaches.…”
Section: Discussionmentioning
confidence: 99%
“…We have been learning that all tumors labeled as H3K27altered DMG globally share the same dismal prognosis: they are aggressive gliomas, not amenable to radical surgery, that respond only to radiotherapy and just for a limited period of time, and then progress lethally in more than 90% of patients within one year (8). Various medical approaches using neoadjuvant or postirradiation chemotherapy have been tested over the decades, but none has demonstrated that it is able to substantially improve OS or PFS, sometimes resulting in increased toxicities and the need for hospitalization (70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, even a preoperative confirmation of malignancy in several diffuse hemispheric gliomas with H3G34 mutation but without imaging features of a high-grade tumor could be achieved by means of 18 F-FET-PET [84]. Especially for those diffuse gliomas without or with questionable features of a higher tumor grade, there is considerable motivation and discussion concerning the general need for a biopsy assessment [78,96]. Several important differential diagnoses for diffuse high-grade gliomas must be addressed, especially from the group of circumscribed astrocytic gliomas.…”
Section: Discussionmentioning
confidence: 99%